Research on a Command Recognition System Based on Artificial Intelligence and Its Application for Air Traffic Control - Shi, Wanli; Zheng, Xiaoqing; Lu, Yong; Zhang, Zhengdong (2023 International Conference on Computer Applications Technology (CCAT), 2023)
The overall goal of the reform of China's civil aviation air traffic control is to build a "four-strong aviation control system (strong safety, strong efficiency, strong intelligence, and strong coordination). Intelligence air traffic control is an important part of the four-strong aviation control system. With the rapid development of civil aviation, the traffic flow of air has continued to increase, and the requirements for the accuracy of command guidance have become increasingly high. Therefore, the introduction of a command recognition system based on artificial intelligence is particularly necessary. This article introduces the main methods of traditional speech recognition technology and their shortcomings in the specialized field of air traffic control, analyzes the advantages of incorporating artificial intelligence into speech recognition technology, and finally provides relevant suggestions for the development of a command recognition system based on artificial intelligence and its application in air traffic control.